2014
DOI: 10.1038/nmat3910
|View full text |Cite
|
Sign up to set email alerts
|

Organo-erbium systems for optical amplification at telecommunications wavelengths

Abstract: Modern telecommunications rely on the transmission and manipulation of optical signals. Optical amplification plays a vital part in this technology, as all components in a real telecommunications system produce some loss. The two main issues with present amplifiers, which rely on erbium ions in a glass matrix, are the difficulty in integration onto a single substrate and the need of high pump power densities to produce gain. Here we show a potential organic optical amplifier material that demonstrates populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 25 publications
3
116
0
3
Order By: Relevance
“…The obtained lifetime decay is best fitted with a dual exponential fit which gives a major lifetime of 0.279 ms whih is in agreement with the values expected for bulk powder [26], but it can be improved up to 0.86 ms [5] by diluting the complexes in order to minimize ion-ion interactions. Such dilution approaches the conditions in which [Er(F-TPIP)3] samples would be prepared for usage in quantum computing [12,27].…”
Section: Luminescencesupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained lifetime decay is best fitted with a dual exponential fit which gives a major lifetime of 0.279 ms whih is in agreement with the values expected for bulk powder [26], but it can be improved up to 0.86 ms [5] by diluting the complexes in order to minimize ion-ion interactions. Such dilution approaches the conditions in which [Er(F-TPIP)3] samples would be prepared for usage in quantum computing [12,27].…”
Section: Luminescencesupporting
confidence: 81%
“…Even more important from the technological point of view is that such composite may be electrically stimulated, in a OLED structure, yielding significant emission from erbium(III) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the low quantum efficiencies that have commonly been achieved in erbium organic materials it is still the case that most of the published work merely demonstrates that some energy transfer must be occurring between the organic and the erbium with few attempts to fully quantify it 21 . In recent works we have used excitation spectroscopy to give some quantification of the integrated sensitisation and demonstrated that it can range from the very low (factor of ~5) 22 to the very high (~10000) 23 . However, the use of excitation spectroscopy only tends to provide data over a limited range of excitation intensities and can be prone to error at high sensitisation due to the difficulty in observing the direct absorption into the ion.…”
Section: Introductionmentioning
confidence: 99%
“…For the organic erbium complex we used erbium(III) tetrakis(pentafluorophenyl)imidodiphosphinate 24 , (Er(F-TPIP) 3 ), which we have demonstrated can have a quantum efficiency of ~7% when deposited by vacuum sublimation in a vacuum of ~10 −7 mbar. For the chromophore we utilised the zinc(II) salt of 2-(3,4,5,6-tetrafluoro-2-hydroxyphenyl)-4,5,6,7-tetrafluorobenzothiazole, Zn(F-BTZ) 2 , which we have already shown can have efficient energy transfer to the erbium ions 23 . We have quantified the sensitisation in a series of films as a function of molar erbium concentrations and developed a simple rate equation model that allows us to not only quantify the sensitisation but also calculate the population of erbium ions in the excited state as a function of excitation pump power.…”
Section: Introductionmentioning
confidence: 99%
“…The erbium-doped fiber or waveguide amplifiers (EDFA or EDWA) represent the standard commercial amplifiers in current optical communication systems [1][2][3][4][5][6][7][8][9]. In such systems, the erbium ions are used as the optically active elements because their intra-4f transition matches well with the standard communication band at 1.54 μm.…”
mentioning
confidence: 99%